2012
DOI: 10.1002/acr.21725
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms and illness perceptions in psoriatic arthritis and associations with physical health‐related quality of life

Abstract: Objective. Symptoms of psychological distress, including anxiety and depressive symptoms, and illness perceptions are important in determining outcome in patients with rheumatic disease. We aimed to compare psychological distress in psoriatic arthritis (PsA) and rheumatoid arthritis (RA) and to test whether the association between psychological variables and health-related quality of life (HRQOL) was similar in the 2 forms of arthritis. Methods. In 83 PsA patients and 199 RA patients, we used the Patient Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
98
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 42 publications
14
98
3
5
Order By: Relevance
“…Lack of sleep and unwanted effects of medication may cause irritability, and with low energy levels patients may withdraw from favoured activities. A cross‐sectional study that included 83 patients with PsA showed an incidence of moderate to severe levels of depressive symptoms in 22% of the cohort 5. Anxiety and concern about bodily symptoms were also seen to affect HRQoL 5.…”
Section: Mitigating the Impact Of Psa On The Patientmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of sleep and unwanted effects of medication may cause irritability, and with low energy levels patients may withdraw from favoured activities. A cross‐sectional study that included 83 patients with PsA showed an incidence of moderate to severe levels of depressive symptoms in 22% of the cohort 5. Anxiety and concern about bodily symptoms were also seen to affect HRQoL 5.…”
Section: Mitigating the Impact Of Psa On The Patientmentioning
confidence: 99%
“…A cross‐sectional study that included 83 patients with PsA showed an incidence of moderate to severe levels of depressive symptoms in 22% of the cohort 5. Anxiety and concern about bodily symptoms were also seen to affect HRQoL 5. Taken together, these factors will negatively influence interpersonal and family relationships, and can contribute to work absenteeism and hence affect career prospects; however, further high quality research is needed to determine the extent of this effect.…”
Section: Mitigating the Impact Of Psa On The Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this review aims to capture various inflammatory rheumatic diseases, it is relevant to mention that most of the studies have been performed in patients with rheumatoid arthritis. Therefore, although studies have shown that quality-of-life impairment and biopsychosocial risk and resilience factors are mostly comparable between diseases [9,10], generalizing the findings to all inflammatory rheumatic conditions should be performed with caution. In addition, we use evidence from healthy controls and patients with other chronic somatic conditions in the case of a lack of studies for inflammatory rheumatic diseases.…”
Section: Introductionmentioning
confidence: 98%
“…Fears about the consequences of the RA were independently correlated to physical HRQOL, i.e., patients who believe in worse consequences of RA had worse scores in the physical component of quality of life measures; patient global assessment of disease activity was also a significant predictor of poor mental and physical HRQOL [6,[33][34][35][36].…”
Section: Patient's Beliefs About Ra Influenced Impact Of Disease and mentioning
confidence: 99%